DINAMIKA MASALAH PEMBANGUNAN KOTA - Rudiansah, Bambang (Ilmu Pemerintahan Universitas Langlangbuana, 2020)
Transfer of agricultural land to non-agricultural functions as a result of the rapid development of the city, brings very complex problems. The complexity of the problem of land use change, among others, can be explained through the perspective of public administration ecology and human ecology, which develops theoretical propositions of a systemic relationship between social systems and ecosystems. Therefore, if agricultural land is converted to non-agricultural activities, it will make it difficult for farmers to transform energy, material and information from social systems to ecosystems and vice versa.The industrial sector or the urban informal sector is not always able to accommodate the energy output from the agricultural sector, which is actually quite available. Therefore, if energy channeling is forced, it is likely to cause energy entropy. It is time for every urban infrastructure development that causes the conversion of agricultural land, efforts need to be made so that the systemic relationship between the social system of farmers and their ecosystems is not shaken. Because in some cases, not all farmers are able to form a new balance, especially so that the process of energy transformation can run normally. In this context, what is theorized by A. Terry Rambo can be a reference for the city government, so that the balance relationship between the two systems is not too much disturbed. More than that, because energy is eternal, what is theorized by Jeremy Rifkin & Ted Howard in his Thermodynamics law, can also be a reference for city governments to regulate the productive use of energy.